Genome sequencing and in silico characterisation of cladosporium sphaerospermum / Yew Su Mei - Yew , Su Mei (2017)
Dematiaceous fungi are a taxonomically diverse group of heterogeneous fungi that are present in the environment. Although rare, many species in this group are known to cause diseases in humans and animals. In this study, a collection of 75 fungal isolates were recovered from various clinical specimens. They were identified through morphology and molecular methods using the internal transcribed spacer (ITS)-based phylogenetic analysis. The complementation of the molecular approach enables the identification of 73 isolates at the species level. The most common species isolated were Cladosporium, Cochliobolus, and Neoscytalidium. Also, 16 isolates from the seven species identified have not been reported to cause human infections. Among the Cladosporium species that were isolated, the species C. sphaerospermum was most frequently isolated. This study was proceeded by whole genome analysis of the C. sphaerospermum, using the strain UM 843 as a study model to explore genetic information and its basic biology. C. sphaerospermum is a ubiquitous saprophytic fungus that has been documented to cause allergy and other opportunistic diseases in humans. Detail characterisation of this isolate has affirmed the identity of UM 843 and its ability to survive in high salt medium (up to 20% NaCl). The genome of UM 843 was generated by combining 500-bp and 5-kb insert libraries, containing 9,652 predicted gene models in the 26.89 Mb genome. Functional annotation of the predicted genes suggests this fungus has the capability to degrade carbohydrate and protein complexes. The abundance of carbohydrate active enzymes (CAZymes) assists in the degradation of hemicellulose and pectin, thus suggesting the precedence of this fungus towards soft plant tissues. Putative genes encoding peptidases from family A01, S09, and M36 that share similarity with Aspergillus peptidases responsible for lung tissue hydrolysis were also identified. UM 843 was also found to carry 16 putative secondary iv metabolite backbone genes, three of these are predicted to be responsible for the synthesis of melanin, siderophores, and cladosins. Besides siderophores, UM 843 contains gene encoding proteins that are involved in iron homeostasis via the reductive iron assimilation (RIA) process. In response to salinity, UM 843 was identified to encode 29 ion transporters and the synthesis of various compatible solutes. The analysis of sexual reproduction suggests that UM 843 is a heterothallic fungus. The genome of UM 843 revealed 28 putative genes associated with C. sphaerospermum allergy. Orthologous gene analysis on UM 843 with 22 other Dothideomycetes showed 125 genes uniquely present in UM 843. Of these, four genes were predicted to encode class 1 hydrophobins which may be allergens specific to Cladosporium. Further analysis showed that the mRNA of the four genes were detected by reverse transcriptionpolymerase chain reaction (RT-PCR). The genomic analysis of C. sphaerospermum UM 843, can significantly contribute to the knowledge of the biology and allergenicity of this species which has not been studied previously